THE DEVELOPMENT MODEL OF BROWN SUGAR MICRO SMALL MEDIUM ENTERPRISE IN SUMBERRINGIN VILLAGE SANAN KULON SUB-DISTRICT BLITAR REGENCY - Arfida Boedirochminarni (Jurnal Ekonomi Pembangunan, 2018)
Blitar Regency is one of the areas in East Java that has become the place for the growth of the food and beverage industry, and has enormous potential. MSME (Micro, Small, Medium Enterprises) in Blitar Regency in 2011 was recorded at 18,644 units. The number then increased significantly in 2015 reaching 254,187 units. One of them is Sumberingin Micro, Small, Medium Enterprises located in the Sumberringin village, Sanan Kulon sub-district, Blitar Regency. These MSMEs seek to improve the economic sector of the region by processing natural resources into goods of the sale value, namely brown sugar. They can produce more than 12kg for each production. Their profits in one production with 12 units get more than IDR 250,000. They have a lot of contributions to their village in increasing the income per capita by producing traditional product to the market and develop their local potential to compete with other modern products through social media marketing and modern market places.